2018
DOI: 10.1108/oth-12-2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

Stressor factors, internal communication and commitment to change among administrative staff in Malaysian public higher-education institutions

Abstract: Purpose The objective of this study is twofold. First, it examines the relationship between stressor factors (i.e. role overload, role conflict, role ambiguity, interpersonal conflict and organizational constraints) and commitment to change. Second, it investigates the moderating effect of internal communication in the hypothesized link. Design/methodology/approach A total of 225 administrative staff in the public higher education institutions located in the Northern Region of Peninsular Malaysia participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Past examinations revealed that there is an adverse connection between work stress and organizational commitment (Pooja, 2016). Notwithstanding, a new report by Zainun et al. (2018) got clashing outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Past examinations revealed that there is an adverse connection between work stress and organizational commitment (Pooja, 2016). Notwithstanding, a new report by Zainun et al. (2018) got clashing outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past examinations revealed that there is an adverse connection between work stress and organizational commitment (Pooja, 2016). Notwithstanding, a new report by Zainun et al (2018) got clashing outcomes. The investigation of Mahmmud et al (2020) uncovered that work pressure factors, in particular, job equivocalness, job over-burden, hierarchical requirements and relational clash impacted the C2C.…”
Section: Leadership and Commitment To Changementioning
confidence: 99%
“…In particular, the current study investigates the ways in which workplace relational conflict alters the relationship between role conflict and emotional exhaustion as well the relationship between role conflict and turnover intention. Previous studies have highlighted the fact that workplace relational conflict negatively affects faculty members’ ability to cope with the role conflict they experiences ( Zainun et al, 2018 ; Krajcsák, 2022 ; Kundi et al, 2022 ), increases their turnover intention ( Vui-Yee and Yen-Hwa, 2020 ; Akhlaghimofrad and Farmanesh, 2021 ; Counts et al, 2021 ), and increases their emotional exhaustion ( Madigan and Kim, 2021 ; Ghasemi et al, 2022 ; Wray and Kinman, 2022 ). To the best of the researcher’s knowledge, no study has investigated the conceptual model proposed by the current study, which aims to address this ongoing gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the active adoption of digital modes of communication allows for faster communication, thereby increasing organisational efficiency (Ahmad and Jasimuddin, 2021). Furthermore, the positive impact of IC in reducing stress levels at work contributes to the smooth implementation and acceptance of changes by employees (Zainun et al , 2018). Research also shows that symmetrical IC with active executive involvement stimulates employee productivity and creativity (Lee and Kim, 2021).…”
Section: Internal Communication In the Asia-pacific Regionmentioning
confidence: 99%